Drug utilization pattern and selected biochemical parameters in pre- and post-hemodialysis state in the end stage renal disease patients: a cross sectional study at a tertiary care hospital - Gokulraj, S. P.; Bouddh, Surendra Kumar; Rajesh, J. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Chronic kidney disease can progress to end-stage kidney failure (ESRD), which is fatal without artificial filtering (dialysis) or a kidney transplant. Methods: The ESRD patients of either gender age >18 years who were diagnosed by nephrologist as ESRD and are on haemodialysis regularly included for the study. Results: The blood urea, serum creatinine, phosphorous, potassium levels were reduced significantly in post – haemodialysis condition, but, there was not much weight reduction after haemodialysis. Serum albumin, serum sodium and blood haemoglobin levels were almost unchanged in post – haemodialysis state. There was no significant difference between the pre and post haemodialysis parameters- serum Na+ serum albumin and blood hemoglobulin. Out of 75 ESRD patients, almost all patients 74 (98.7%) prescribed tablet Livogen, 73 (97.3%) patients given Inj. EPO, 55 (73.3%) tab Nicardia, 54 (76%) tab Sodamint, 43 (57.3%) capsule Alpha D3, 40 (53.3%) tab Shelcal. While between 12 (16%) to 20 (26%) patients prescribed tab Nodosis, tab Metoprolol, tab Febuget, tab Ecosprin, and tab Rantac. Only 1 (1.3%) to 9 (12%) patients received tablet Augmentin, tab Arkamine, tab Carvedilol, tab Para 500, tab Atorvas, Human mixtard, tab Calcicard, tab Minipress XL, tab Dytor, and tab Clopilet. Conclusions: The available two models of treatment, i.e., haemodialysis and poly pharmacy at hospital setup to face the challenges associated with the ESRD, and even outcome after application of both these two models of therapies did not provide optimal normal healthy life status to ESRD patients.